Respiratory rate and its associations with disease and lifestyle factors in the general population – results from the KORA-FF4 study - Ina-Maria Rückert-Eheberg; Alexander Steger; Alexander Müller; Birgit Linkohr; Petra Barthel; Melanie Maier; Julia Allescher; Moritz F. Sinner; Konstantinos D. Rizas; Wolfgang Rathmann; Karl-Ludwig Laugwitz; Stefan Kääb; et al. (PLoS ONE, 2025)
Objective The aim of the study was to derive median age- and sex-specific respiratory rates in a population-based sample of adults and to identify disease and lifestyle factors associated with elevated respiratory rates. Methods In the population-based KORA FF4 study conducted in Augsburg, Germany, 5-minute 12-lead resting electrocardiograms (ECGpro-system, AMEDTEC) were recorded in 2,224 participants from 39 to 88 years. Respiratory rate was derived from these electrocardiograms. Sex- and age-specific medians, IQRs, and percentiles were calculated. Associations of sociodemographic, disease, and lifestyle variables with elevated resting respiratory rate were assessed by univariable and multivariable logistic regression analyses. Results Respiratory rate decreased slightly from youngest to middle-aged women and men and increased in old age. Overall, median (IQR) was 15.80 (3.16) breaths per minute (brpm). Five percent of the participants had values lower than 12.06 brpm, and five percent had values above 20.06 brpm (95th percentile). Elevated respiratory rates of ≥  18.6 brpm were found in 13.8% (n =  308). In an adjusted logistic regression model, age, abdominal obesity, diabetes, COPD, smoking, and low education were significantly associated with elevated respiratory rate. Stratified analyses showed that education appeared to be more relevant in women, while the effect of diabetes was more pronounced in men. Conclusions High respiratory rate may be an indicator of impaired health in the general population, especially regarding pulmonary and metabolic characteristics, and unfavorable lifestyle and living conditions. Individuals with an increased respiratory rate should therefore be examined and followed up more closely to recognize diseases and adverse progressions at an early stage and to possibly prevent them.